2003
DOI: 10.1038/sj.gt.3302059
|View full text |Cite
|
Sign up to set email alerts
|

Mutational effects of retrovirus insertion on the genome of V79 cells by an attenuated retrovirus vector: implications for gene therapy

Abstract: Attenuated retroviruses are currently the most widely used vectors in clinical gene therapy because of their potential to effect stable and permanent gene transfer. Since gene delivery is accompanied by random insertion of foreign genetic material into the recipient chromosomal DNA, the potential for insertional mutagenesis exists. In this study, we used a defective retrovirus vector containing a selectable marker, the hygromycin phosphotransferase gene, to investigate the mutagenic effects of vector integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Chromosomal instability was found to occur at the site of integration of the Cyp2b1 expression vector. In another report, V79 cells were treated with an attenuated retrovirus [Themis et al, 2003], wherein an increased mutation rate at the Environmental and Molecular Mutagenesis. DOI 10.1002/em Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Chromosomal instability was found to occur at the site of integration of the Cyp2b1 expression vector. In another report, V79 cells were treated with an attenuated retrovirus [Themis et al, 2003], wherein an increased mutation rate at the Environmental and Molecular Mutagenesis. DOI 10.1002/em Fig.…”
Section: Discussionmentioning
confidence: 98%
“…A BLAST search demonstrates that the virus-derived sequences present in the CKR introns are in fact present at many other sites in the human genome. For instance, a BLAST search (without filter for low complexity regions) for the HERV-H/env60 sequence, of which a homolog is present in the CCR10 intron (290 nt; 85% conserved; 4.E-88; Table 1), yielded 34,192 Blast Hits with E values equal to or lower than the virus/CKR alignment. Thus, it may be concluded that the question, whether CKRs were primarily infected or other genes were first infected and then a SINE duplicated itself in some of CKR gene introns, cannot at present be answered.…”
Section: Discussionmentioning
confidence: 99%
“…(31,32) Potential genotoxicity of retroviral integration is also discussed in. (33)(34)(35)(36)(37)(38)(39)(40) In still other instances, sequences of infecting retroviruses, after reverse transcription, became permanently integrated into the intronic genome of germ-line cells and are thus transmitted in a Mendelian manner: these sequences are generally referred to as "endogenous retroviruses" (ERVs) or more specifically "human ERVs" (HERVs) if present in the human genome. (41)(42)(43)(44)(45) Such sequences are widespread in many animal species, including humans, in which they are estimated to account for 1-5% of the genome.…”
Section: Research Articlementioning
confidence: 99%
“…7 The reversal of eNOS downregulation by L-NIL suggests a NOS dependent mechanism of eNOS downregulation, and not a non-specific effect of retroviral gene transduction such as insertional mutation. 21,22 The elevated nitrite levels measured in the iNOStransduced EC, but not L-NIL treated cells, support a mechanism related to NO or one of its downstream mediators. However, iNOS overexpression could also downregulate eNOS via a superoxide-mediated mechanism, independent of NO.…”
Section: Discussionmentioning
confidence: 99%